The dice have no dots - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Never genteel, making a living from commodities has now become a hopeless, hurting game. There are three ways out: horizontally,jump, or sit on a hedge.December 2001. The cocoa market of Mbanga, north-west of Douala, Cameroon s major port, is being...